Distribution patterns of scorpions of the Andean region of southern Peru - Ochoa, José Antonio (2005)
The geographical distribution of 24 scorpion species (five genera and three families) from the Andean corridor in southern Peru is provided. Some zoogeographic details of the implicated species are discussed (19 are exclusive from the area); these species are grouped into seven scorpiological areas: Desierto costero, Serranía esteparia, Puna, Queswa, Valles interandinos cálidos, and Yungas. The Lomas, Serranía esteparia and Queswa areas, are the areas with the most richness of species. The distribution patterns of species, which suggests the presence of three faunistic components in southern Peru: andean-patagonian, amazonian and caribbean, are analysed.